The coming crisis: obtaining care for the growing burden of neurodegenerative conditions - Dorsey, E Ray; George, Benjamin P; Leff, Bruce; Willis, Allison W (Neurology, 2013)
As the U.S. population ages, the burden of neurodegenerative disorders, including Alzheimer disease and Parkinson disease, will increase substantially. However, many of these patients and their families currently do not receive neurologic care. For example, a recent study found that over 40% of Medicare beneficiaries with an incident Parkinson disease diagnosis did not receive neurologist care early after diagnosis and those who did not were more likely to fracture a hip, be placed in a nursing home, and die. While geography, age, race, and sex likely contribute to these observed disparities in care and outcomes, a large barrier may be Medicare's reimbursement policies, which value procedures over care. With further reductions in Medicare reimbursement constantly on the horizon, the devaluing of clinical care will likely continue. Rather than guaranteeing access to care, Medicare's reimbursement policies may increasingly be an impediment to care.